2023
DOI: 10.3389/fpls.2023.1103857
|View full text |Cite
|
Sign up to set email alerts
|

An improved reference genome for Trifolium subterraneum L. provides insight into molecular diversity and intra-specific phylogeny

Abstract: Subterranean clover (Trifolium subterraneum L., Ts) is a geocarpic, self-fertile annual forage legume with a compact diploid genome (n = x = 8, 544 Mb/1C). Its resilience and climate adaptivity have made it an economically important species in Mediterranean and temperate zones. Using the cultivar Daliak, we generated higher resolution sequence data, created a new genome assembly TSUd_3.0, and conducted molecular diversity analysis for copy number variant (CNV) and single-nucleotide polymorphism (SNP) among 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…These assemblies will facilitate marker-assisted breeding programs for traits of agronomic importance and provide increased resolution and ability to identify the genomic basis of adaptation in this increasingly used model in evolutionary ecology and genetics. Together with an alternative and upcoming chromosome-level assembly ( Wang et al 2023 ) and other high-quality reference genomes in the genus ( Dluhošová et al 2018 ; Bickhart et al 2022 ; Shirasawa et al 2023 ), our haplotype-resolved assembly will be particularly useful for identifying structural variation and facilitate the development of pangenomic references ( Eizenga et al 2020 ) for which haplotype-resolved assemblies are an asset ( Garg et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These assemblies will facilitate marker-assisted breeding programs for traits of agronomic importance and provide increased resolution and ability to identify the genomic basis of adaptation in this increasingly used model in evolutionary ecology and genetics. Together with an alternative and upcoming chromosome-level assembly ( Wang et al 2023 ) and other high-quality reference genomes in the genus ( Dluhošová et al 2018 ; Bickhart et al 2022 ; Shirasawa et al 2023 ), our haplotype-resolved assembly will be particularly useful for identifying structural variation and facilitate the development of pangenomic references ( Eizenga et al 2020 ) for which haplotype-resolved assemblies are an asset ( Garg et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These assemblies will facilitate marker-assisted breeding programs for traits of agronomic importance and provide increased resolution and ability to identify the genomic basis of adaptation in this increasingly used model in evolutionary ecology and genetics. Together with an alternative and upcoming chromosome-level assembly [67] and other high-quality reference genomes in the genus [68][69][70], our haplotype-resolved assembly will be particularly useful for identifying structural variation and facilitate the development of pangenomic references [71] for which haplotype-resolved assemblies are an asset [72].…”
Section: Discussionmentioning
confidence: 99%
“…Genomics is a promising tool for accelerating breeding programs by playing a crucial role in the rapid development of new varieties and ensuring resilience and adaptability in changing climates (Thudi et al, 2021). Although genome information on red clover, white clover, and subterranean clover is publicly available (Sato et al, 2005;Isobe et al, 2012;Bickhart et al, 2022;Santangelo et al, 2023;Shirasawa et al, 2023), no genome data for Egyptian clover have been reported thus far, except for the chromosome number of 2n = 2x = 16 (Wexelsen, 1928).…”
Section: Introductionmentioning
confidence: 99%